Land use alters the resistance and resilience of soil food webs to drought - de Vries, Franciska T.; Liiri, Mira E.; Bjørnlund, Lisa; Bowker, Matthew A.; Christensen, Søren; Setälä, Heikki M.; Bardgett, Richard D. (Nature climate change, 2012)
A study shows that soil food webs directly help mitigate the effects of drought on soil nutrients. The fungal-based food webs of grassland were more resistant to bouts of drought than the bacterial-based food webs of intensively managed wheat, and retained more carbon and nitrogen in the soil. Soils deliver several ecosystem services including carbon sequestration and nutrient cycling, which are of central importance to climate mitigation and sustainable food production 1 , 2 , 3 . Soil biota play an important role in carbon and nitrogen cycling, and, although the effects of land use on soil food webs are well documented 4 , 5 , 6 , the consequences for their resistance and resilience to climate change are not known. We compared the resistance and resilience to drought—which is predicted to increase under climate change 2 , 7 —of soil food webs of two common land-use systems: intensively managed wheat with a bacterial-based soil food web and extensively managed grassland with a fungal-based soil food web. We found that the fungal-based food web, and the processes of C and N loss it governs, of grassland soil was more resistant, although not resilient, and better able to adapt to drought than the bacterial-based food web of wheat soil. Structural equation modelling revealed that fungal-based soil food webs and greater microbial evenness mitigated C and N loss. Our findings show that land use strongly affects the resistance and resilience of soil food webs to climate change, and that extensively managed grassland promotes more resistant, and adaptable, fungal-based soil food webs.